Evaluation of serum lipids in preeclampsia: a comparative study - Thathagari, Varija; C. M., Veerendra Kumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Preeclampsia occurs in 7 to 10% of pregnancies worldwide. At present most, popular theory is an oxidative stress. Abnormal lipid profiles and species may have a role in promotion of oxidative stress and vascular dysfunction seen in pre-eclampsia. Objectives of this study was carried out to evaluate lipid profile in subjects with preeclampsia and to compare lipid profile in subjects of preeclampsia as compared to normal pregnant women. Methods: A comparative longitudinal study was conducted under the tertiary care hospital setting over a period of one year where 440 study subjects were enrolled out of which 220 subjects were pre-eclamptic and 220 subjects were normotensive with gestation of 28 weeks to till term. Lipid profiling was done in all the subjects. Results: The mean serum levels of total cholesterol (198.5±18.91), HDL (50.63±9.35), LDL (84.5±16.16), VLDL (42.75±4.72) and TGA (74.92±11.95) were higher in pre-eclampsia group compared to normotensive group and this difference in the levels of lipid parameters was found to be statistically significant. Conclusions: Dyslipidemia is significantly evident in preeclampsia and plays an important role in its pathogenesis.